2006
DOI: 10.1210/me.2006-0090
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor-I Induces α1B-Adrenergic Receptor Phosphorylation through Gβγ and Epidermal Growth Factor Receptor Transactivation

Abstract: IGF-I induces alpha(1B)-adrenoceptor (alpha(1B)-AR) phosphorylation. The effect of IGF-I was rapid and transient, reaching near-maximal values at 10 min and decreasing after 30 min; it was observed at low IGF-I concentrations (EC(50) approximately 10 ng/ml) and was associated to receptor desensitization as evidenced by a decreased alpha(1B)-adrenergic effect on intracellular calcium and production of inositol phosphates. The effect of IGF-I was markedly decreased in cells treated with pertussis toxin suggestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 44 publications
3
22
0
1
Order By: Relevance
“…More recently, it has been demonstrated that for certain G protein-coupled receptor-mediated increases in intracellular calcium concentration (vasopressin, bradykinin, angiotensin II, neurotensin, and bombesin) insulin can enhance rather than inhibit signaling via a mammalian target of rapamycin-dependent pathway (32,33). However, our data demonstrating an insulin-mediated decrease rather than an increase in PAR 2 -triggered calcium signaling are in keeping with the ability of insulin-like growth factor I and insulin to induce phosphorylation and desensitization of the G protein-coupled a 1B and a 1D adrenergic receptors (34,35). In those studies, as in ours, inhibitors of PI3K and PKC blocked receptor phosphorylation (on serines in the a 1D adrenoceptor) caused by the growth factors.…”
Section: Discussionsupporting
confidence: 74%
“…More recently, it has been demonstrated that for certain G protein-coupled receptor-mediated increases in intracellular calcium concentration (vasopressin, bradykinin, angiotensin II, neurotensin, and bombesin) insulin can enhance rather than inhibit signaling via a mammalian target of rapamycin-dependent pathway (32,33). However, our data demonstrating an insulin-mediated decrease rather than an increase in PAR 2 -triggered calcium signaling are in keeping with the ability of insulin-like growth factor I and insulin to induce phosphorylation and desensitization of the G protein-coupled a 1B and a 1D adrenergic receptors (34,35). In those studies, as in ours, inhibitors of PI3K and PKC blocked receptor phosphorylation (on serines in the a 1D adrenoceptor) caused by the growth factors.…”
Section: Discussionsupporting
confidence: 74%
“…The procedure employed to study α 1B -AR phosphorylation, has been previously described in detail [15, 16, 18]. In brief, cells were maintained overnight in phosphate-free Dulbecco’s modified Eagle’s medium without serum.…”
Section: Methodsmentioning
confidence: 99%
“…These proteases cause shedding of HB-EGF from the plasma membrane and subsequent activation of EGF receptor intrinsic tyrosine kinase, resulting in the triggering of intracellular signaling [20, 21]. Surprisingly, this process is much more general than we could have anticipated and is involved in both homologous and heterologous desensitization and phosphorylation of α 1B -ARs [9, 10, 15, 16]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations